2021
DOI: 10.18371/fcaptp.v1i36.227628
|View full text |Cite
|
Sign up to set email alerts
|

Controlling of Trade Enterprises in the Context of the International Dimension

Abstract: The article deals with the features of the controlling implementation in trade enterprises in the context of the international dimension, the possibility of adapting international approaches to the Ukrainian conditions of business. The essential concept of controlling and its connection with realization of the general functions of management is defined. It is established that controlling is a management subsystem that ensures the achievement of the mission and system of goals of the enterprise, covers all area… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 2 publications
0
1
0
3
Order By: Relevance
“…In the strategic area, they prefer tools similar to Taran, based on detailed analyses. Lositska et al (2022) solved the problem with controlling implementation in trade enterprises and found that for economic efficiency it is important to use tools such as benchmarking, ABS and XYZ-analyses, outsourcing matrix, DPS method, profitability chart "Maisigma" and also the introduction of control mechanisms. The variety of existing tools suggests that the issue in question is designed quite profoundly and many factors determine its practical status.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In the strategic area, they prefer tools similar to Taran, based on detailed analyses. Lositska et al (2022) solved the problem with controlling implementation in trade enterprises and found that for economic efficiency it is important to use tools such as benchmarking, ABS and XYZ-analyses, outsourcing matrix, DPS method, profitability chart "Maisigma" and also the introduction of control mechanisms. The variety of existing tools suggests that the issue in question is designed quite profoundly and many factors determine its practical status.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Дослідження й розвиток теорії фінансового контролінгу здійснили провідні вітчизняні й зарубіжні вчені: К. Друрі, О. О. Терещенко, С. Фалько, Д. Хан, П. Хорват, Т. В. Паєнтко, В. М. Федосов та ін. Основні аспекти впровадження інструментів фінансового контролінгу у практичну діяльність підприємств торгівлі розглядаються у публікаціях таких вчених-економістів, як Л. О. Лігоненко, О. А. Вержбицький [1], Т. І. Лосіцька, В. Д. Лагутін, Т. М. Мельник [2], В. М. Костюченко, А. В. Каміл (Купрієнко) [3; 4], А. В. Сисоєв [5], М. В. Тарасюк [6].…”
Section: анотаціяunclassified
“…[3], Лосіцька Т.І., Бєляєва Н.С., Лагутін В.Д., Мельник Т.М. [4], Костюченко В.М, Каміл (Купрієнко) А.В. [5; 6], Сисоєв А.В.…”
unclassified
“…Коптелов та В.В. Крохін [4] наголошують на необхідності та процедурі використання інформаційних систем ERP-класу для реалізації на підприємстві концепції контролінгу бізнес-процесів.…”
unclassified